The Relationship between Adolescent Girls' Behavior on Reproductive Health and the Motivation to Do Premarital Health Examinations - Ulin Nikmah; Iis Hanifah; Mega Silvian Natalia (Health and Technology Journal (HTechJ), 2023)
Reproductive health is the starting point for developing maternal and child health, which can be prepared early, even before a woman becomes pregnant and a mother. Preconceptional health is part of the overall health between women and men during their reproductive years. This study analyzes the relationship between adolescent girls' behavior on reproductive health and motivation to conduct premarital health examinations in Gading Kulon Village, Probolinggo. This quantitative research design with a correlational design using a study approach across sectional with 34 respondents using an accidental sampling technique. Data collection included coding, editing, and tabulating, then analyzed manually and by computer with Spearman Rank. Based on data from 34 respondents, most of the behavior of young women regarding reproductive health was lacking; 22 respondents (64.7%) included motivation to carry out premarital examinations, namely two respondents (5.9%) were good, 14 respondents (41.2%) sufficient, while 18 respondents were lacking (52.9%) was found p=0.002, there is a relationship between female adolescent behavior regarding reproductive health with motivation to carry out premarital health checks in Gading Kulon Village, Probolinggo. Therefore, the existence of youth groups must be addressed.